Reviewer Acknowledgements for Environmental Management and Sustainable Development, Vol. 10 No. 3 - Young, Jenny (Environmental Management and Sustainable Development, 2021)
Environmental Management and Sustainable Development (EMSD) would like to thank the following reviewers for reviewing manuscripts from May 1, 2021, to August 1, 2021. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Many authors, regardless of whether EMSD publishes their work, appreciate the helpful feedback provided by the reviewers. Macrothink Institute appreciates the following reviewers’ rigorous and conscientious efforts for this journal. Each of the reviewers listed below returned at least one review during this period. Adriano Magliocco, University of Genoa, Italy Aristotulus Ernst Tungka, University of Sam Ratulangi Manado, Indonesia Christiane do Nascimento Monte, Universidade Federal Fluminense, Brazil Chuck Chuan Ng, Xiamen University Malaysia, Malaysia Dastun Gabriel Msuya, Sokoine University Of Agriculture, Tanzania Giacomo Chiesa, Politecnico di Torino, Italy Jephias Mapuva, Bindura University, Zimbabwe João Fernando Pereira Gomes, Instituto Superior de Engenharia de Lisboa, Portuguese Md. Nuralam Hossain, Chongqing University, China Oylum Gokkurt Baki, Sinop University, Turkey Pankaj Maheshwari, University of Nevada, USA Tateda Masafumi, Toyama Prefectural University, Japan